2021
DOI: 10.3390/nu13124562
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate (MTHFR), the One-Carbon Cycle, and Cardiovascular Risks

Abstract: The 5-10-methylenetetrahydrofolate reductase (MTHFR) enzyme is vital for cellular homeostasis due to its key functions in the one-carbon cycle, which include methionine and folate metabolism and protein, DNA, and RNA synthesis. The enzyme is responsible for maintaining methionine and homocysteine (Hcy) balance to prevent cellular dysfunction. Polymorphisms in the MTHFR gene, especially C677T, have been associated with various diseases, including cardiovascular diseases (CVDs), cancer, inflammatory conditions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
1
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 115 publications
1
67
1
9
Order By: Relevance
“…Accelerating folate circulation can increase the activity of MTHFR or directly enrich folic acid, suggesting that folic acid supplementation may regulate ACE2 expression. Lack of MTHFR expression causes elevated homocysteine levels, which in turn leads to an increased risk of thrombosis and is associated with a higher risk of cardiovascular disease ( Raghubeer and Matsha, 2021 ). This may explain why people with underlying cardiovascular disease tend to become sicker after contracting a respiratory virus.…”
Section: Discussionmentioning
confidence: 99%
“…Accelerating folate circulation can increase the activity of MTHFR or directly enrich folic acid, suggesting that folic acid supplementation may regulate ACE2 expression. Lack of MTHFR expression causes elevated homocysteine levels, which in turn leads to an increased risk of thrombosis and is associated with a higher risk of cardiovascular disease ( Raghubeer and Matsha, 2021 ). This may explain why people with underlying cardiovascular disease tend to become sicker after contracting a respiratory virus.…”
Section: Discussionmentioning
confidence: 99%
“…The MTHFR gene, in which inherited mutations can influence an optically active enzyme and, accordingly, elevated homocysteine levels ( 18 ), functions in the folate-homocysteine metabolic pathway and has an impact on protein, DNA, and RNA synthesis. The enzyme, therefore, is in charge of maintaining the balance of folic and homocysteine to prevent dysfunction in cells ( 11 ). Population-based studies have demonstrated a sound association of MTHFR genetic variants with the risk of CHD ( 19 , 20 ); however, results of previous studies on this topic have been dissident, with the majority restricted to a minor number of functional non-synonymous polymorphisms ( 21 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the genetic polymorphisms rs1801133 (C667T) and rs1801131 (A1298C) of the MTHFR gene piqued interest. The rs1801133 MTHFR polymorphism affected the optimal activity of the enzyme ( 11 ) and increased the level of homocysteine ( 8 ) and the other variation ( MTHFR A1298C) within the presumed regulatory domine also inhibited the enzyme activity ( 12 ). It is worth noting that findings from previous studies involved in the association of the two genetic mutations with the risk of CHD were conflicting ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…With insufficient absorption and impaired transport, consequences could be manifold, including immunologic and neurologic dysfunctions (Kronn & Goldman, 2008). Methylene tetrahydrofolate reductase (MTHFR), which converts 5,10‐methylene‐THF to 5‐methyl‐THF (Figure 3b), contributes to Met generation from Hcy and thus plays a crucial role in maintaining cellular folate homeostasis and the 1C pool (Raghubeer & Matsha, 2021). Gene variants of MTHFR, particularly the C677T polymorphism, are quite common among human populations and are thought to be related to certain diseases, such as cardiovascular diseases (CVDs), and pose a higher risk of neural tube defects (NTDs) (Tsang et al., 2015).…”
Section: The Vitamin B9 Familymentioning
confidence: 99%